Native Peoples of the American Continent (Eskimos) - Noori, Sima (Journal of Natural Sciences – Kabul University, 2025)
In the very distant past, some people migrated from Asia and Mongolia to undiscovered territories, reaching the present-day Bering and Greenland areas and settling there for some time. These people have short, wide limbs with shorter arms and legs than usual, and their eyes are wide open. Eskimos are traditionalists who live according to their specific rituals and traditions. Around the North Pole, there are people who call themselves Inuit. The current number of Inuit people, often known as Eskimos, is about 100,000. The Eskimo hunting tools were very basic in the past, but they continue to hunt and survive today. Despite the pressures of modern development in the North, Eskimos have been able to maintain their traditional social and cultural roots and continue to live on the land of their ancestors.